Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10722-010-9561-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two novel Glu-D1-encoded subunits from Chinese wheat (Triticum aestivum L.) landrace and functional properties of flours possessing the two novel subunits

Abstract: The high molecular weight glutenin subunits (HMW-GS) can be used for wheat quality improvement. Two novel alleles (designated 1Dx1.5* and 1Dy12.2*, respectively) at the Glu-D1 locus were identified in the Chinese wheat landrace variety 'Jiuquanjinbaoyin' by comparison of subunit mobility with that previously identified in several standard hexaploid wheats. The 1Dx1.5* and 1Dy12.2* genes were isolated using the allele-specific PCR primers and the complete open reading frames (ORFs) were obtained. Allele 1Dx1.5*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Glu-D1d (5+10) is a HMW-GS allele conferring better quality (Guo et al, 2010). Positive effect of Glu-D1d was present on the genotypes used in this study.…”
Section: High and Low Molecular Weight Glutenin Subunits (Hmw-gs And mentioning
confidence: 73%
“…Glu-D1d (5+10) is a HMW-GS allele conferring better quality (Guo et al, 2010). Positive effect of Glu-D1d was present on the genotypes used in this study.…”
Section: High and Low Molecular Weight Glutenin Subunits (Hmw-gs And mentioning
confidence: 73%
“…Another three HMWGSs were identified in hexaploid wheat (genome AABBDD), with two in T. aestivum L., the 1Dy12* subunit in the Slovak obsolete cultivar Trebišovská (GenBank accession: EU266533, Mihálik & Gregová, unpublished) and the subunit 1Dy12.2* in the Chinese landrace Jiuquanjinbaoyin (GenBank: FJ226583, Guo et al 2010), and the third subunit (1Dy10.1) in T. petropavlovskyi Udacz. et Migush (GenBank: AY695379, Jiang et al 2006).…”
mentioning
confidence: 99%
“…Different resistance and tolerance genes as well as glutenin genes related to quality from the landraces are found (Guo et al 2010;Lan et al 2013;Xiao et al 2013a, b). As a result, these wheat landraces can be exploited in wheat cultivar improvement programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The subunits 1Ax2*, 1Dx5?1Dy10, 1Bx17?1By18 are positively associated with bread-making qualities in contrast with null, 1Dx2?1Dy12, 1Bx7?1By8 (Branlard and Dardevet 1985;Payne 1987;Rogers et al 1989). The characterization of such quality related to HMW subunits in bread wheat leads to searching for new alleles of HMW-GS in common wheat and its related species (Wan et al 2002;Wang et al 2004;Cong et al 2007;Pang and Zhang 2008;Guo et al 2010;Jiang et al 2005Jiang et al , 2010Jin et al 2012;Ma et al 2013;Xiao et al 2014). Considerable numbers of studies showed that alleles of HMW-GS at one individual locus are rich in Chinese wheat landraces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation